Chinese Herbal Medicine Combined With First-Generation EGFR-TKIs in Treatment of Advanced Non-Small Cell Lung Cancer With EGFR Sensitizing Mutation: A Systematic Review and Meta-Analysis - Lu, Yan; Sun, Chenbing; Jiao, Lijing; Liu, Yu; Gong, Yabin; Xu, Ling (Frontiers in Pharmacology, 2021)
Background: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide. First-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKIs) significantly improve prognosis of advanced NSCLC patients harboring EGFR sensitizing mutation. However, acquired resistance to EGFR-TKIs limits the good outcomes. Chinese herbal medicine (CHM) has been used for NSCLC patients receiving EGFR-TKIs for more than 10 years as an adjuvant treatment. Methods: Studies were searched from China BioMedical Literature, Chinese National Knowledge Infrastructure, Cqvip Database, Wanfang Database, MEDLINE (PubMed), EMBASE (Ovid), Google Scholar, and Cochrane Library from inception to March, 2021. Randomized controlled clinical trials (RCT) comparing EGFR-TKIs + CHM (TKIs + CHM) versus EGFR-TKIs with/without placebo (TKIs ± placebo) in participants with advanced NSCLC patients harboring EGFR sensitizing mutation were included in this study. Two authors screened all references, assessed the risk of bias and extracted data independently. Data were summarized using hazard ratio (HR) and risk ratios (RR), with 95% confidence intervals (CI) for binary outcomes. Meta-analysis was performed using random effects model. Overall quality of evidence was assessed using GRADE. Results: A total of 9 RCTs (1137 participants, 581 in the TKIs + CHM group and 556 in the TKIs ± placebo group) were included in this review. Only first-generation EGFR-TKIs were included. Most trials included used oral CHM preparations to tonify Qi and/or Yin. Treatment lasted from enrollment until disease progression (PD) or intolerable adverse events (AE). Combination of CHM with EGFR-TKIs improved median progression-free survival (mPFS) (HR, 0.59; 95% CI, 0.52-0.68; P < 0.00001) and objective response rate (ORR) (RR, 1.23; 95% CI, 1.13-1.34; P < 0.00001) compared with used of EGFR-TKIs ± placebo. CHM reduced AE associated with EGFR-TKIs such as cutaneous toxicity (RR, 0.67; 95% CI, 0.52-0.85; P =0.009), diarrhea (RR, 0.43; 95% CI, 0.30-0.60; P <0.00001). Conclusions: Combination therapy of CHM and EGFR-TKIs significantly delays acquired resistance while improving ORR to EGFR-TKIs. Furthermore, CHM reduces AE induced by EGFR-TKIs. More international multi-centered, double-blinded, placebo-controlled, well-designed clinical trials are needed in future research.